1991
DOI: 10.1080/00207549108930056
|View full text |Cite
|
Sign up to set email alerts
|

A new approach for project scheduling with a limited resource

Abstract: Eight priority rules for ranking activities of a project under a limited resourceare proposed. The capabilities of these rules are compared using five measures of performance by employing the set of networksused by Elsayedand Nasr (1986). A new scheduling heuristic, SEARCH, that selects the shortest duration schedule produced by one of the eight priority rules is proposed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

1991
1991
2006
2006

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 8 publications
0
10
0
Order By: Relevance
“…Different computing models for the priorities by taking into account these factors will characterize the corresponding priority rules and may lead to different performances. Because there is no systematic measure to select a heuristic rule or to decide which is better than others [9], a multiple-pass heuristic method that considers different priority rules for each pass is proposed so as to select the best one among multiple solutions [7,18,19]. Moreover, a local search way for an improved solution by adjusting start times of some activities based on the current multiple-solutions from the multiple-pass heuristic is recommended [20].…”
Section: Particle-represented Priorities Of Activitiesmentioning
confidence: 98%
“…Different computing models for the priorities by taking into account these factors will characterize the corresponding priority rules and may lead to different performances. Because there is no systematic measure to select a heuristic rule or to decide which is better than others [9], a multiple-pass heuristic method that considers different priority rules for each pass is proposed so as to select the best one among multiple solutions [7,18,19]. Moreover, a local search way for an improved solution by adjusting start times of some activities based on the current multiple-solutions from the multiple-pass heuristic is recommended [20].…”
Section: Particle-represented Priorities Of Activitiesmentioning
confidence: 98%
“…Although many individual priority rules have been devised, it is reported that there is no priority rule that dominates others or performs consistently better than other rules. 5,6 To cope with such weakness of individual rules, Boctor 7 and Khattab and Choobineh 6 suggest composite heuristics that include several priority rules and select the best solution among those from the individual rules as the ®nal solution.…”
Section: Introductionmentioning
confidence: 99%
“…There are some recent studies [1,13] that are wmrthy to mention here because of their different approaches. Bell et.al.…”
Section: 3 1 Heui'istic Approachesmentioning
confidence: 99%
“…They were given by Wiest [29] and Fendly [10]. There are several attempts including comparative studies in between the e.xisting heuristics and between the heuristics and the optimal solution procedures [1,2,4,7,9,10,12,13,15,18,19,28,29].…”
Section: 3 1 Heui'istic Approachesmentioning
confidence: 99%
See 1 more Smart Citation